Usefulness of metalloproteinase‐9 and tissue inhibitor of metalloproteinase‐1 in clinical characterisation of children with newly diagnosed Crohn's disease. (4th May 2020) - Daniluk, Urszula; Daniluk, Jaroslaw; Guzinska‐Ustymowicz, Katarzyna; Pryczynicz, Anna; Lebensztejn, Dariusz
Abstract : Aim: The aim of this study was to determine the relation of non‐invasive markers representing gut mucosal damage (metalloproteinase‐9 (MMP‐9)) and remodelling (tissue inhibitor of metalloproteinase‐1 (TIMP‐1)) with Crohn's disease (CD) phenotype, disease activity scores (clinical and endoscopic) and radiological evaluation of the ileum in newly diagnosed children. Methods: Serum and faecal MMP‐9 and TIMP‐1 concentrations were determined with the sandwich enzyme‐linked immunoassay technique. The performance of each marker with reference to the Paris classification, disease activity scores and magnetic resonance enterography results was assessed using non‐parametric tests. Results: A total of 32 children with CD demonstrated higher levels of serum and faecal MMP‐9 and TIMP‐1 compared with a control group including children without gastrointestinal inflammatory disease (all P  < 0.05). Only the serum MMP‐9 concentration was significantly higher in children with L3 (ileocolonic) compared with children with L1 (distal ileum). The serum TIMP‐1 level was significantly higher in patients with an magnetic resonance enterography‐detected ileum involvement longer than 51 mm and in children with severe disease activity compared with other patients. The serum MMP‐9 level was lower in patients with stenosis combined with prestenotic dilation compared with children without stenosis. Conclusion: Increased serum and faecal MMP‐9 and TIMP‐1 concentrations are some reliable markers of inflammation in newly diagnosed children with CD, but without facilitating clear phenotyping of the disease.